Immune evaluation of granulocyte-macrophage colony stimulating factor loaded hierarchically 3D nanofiber scaffolds in a humanized mice model - Chen, Rui; Li, Yujie; Zhuang, Yangyang; Zhang, Yiming; Wu, Hailong; Lin, Tao; Chen, Shixuan (Frontiers in Bioengineering and Biotechnology, 2023)
Immune evaluation of biomaterials for tissue regeneration is a critical preclinical evaluation. The current evaluation criterion (ISO 10993-1 or GB/T 16886) uses rodents to perform the immune evaluation. However, the immune system of rodents is different from humans, the obtained results may not be reliable, which could lead directly to the failure of clinical trials.In the presented study, significantly cell migration and extracellular matrix deposition were observed in the 3D radially aligned nanofiber scaffold. The locally released GM-CSF could accelerate the expression of human dendritic cells (CD11c) only 3 days after subcutaneous implantation. Moreover, higher expression of human cytotoxic T cell (CD3+/CD8+) was detected within GM-CSF loaded radially aligned nanofiber scaffolds and their surrounding tissues. Granulocyte-macrophage colony-stimulating factor (GM-CSF) shows a great potential application in tissue regeneration by regulating local immune responses. The presented work combines the advantages of GM-CSF (immunoregulation) and hierarchically 3D nanofiber scaffolds (tissue regeneration).